Developments in the design and delivery of self‐management support for children and young people with diabetes: A narrative synthesis of systematic reviews. Issue 4 (6th January 2023) - Litchfield, Ian; Barrett, Timothy; Hamilton‐Shield, Julian P.; Moore, T. H. M.; Narendran, Parth; Redwood, Sabi; Searle, Aidan; Uday, Suma; Wheeler, Jess; Greenfield, Sheila
Abstract: Aims: Facilitated self‐management support programmes have become central to the treatment of chronic diseases including diabetes. For many children and young people with diabetes (CYPD), the impact on glycated haemoglobin (HbA1c ) and a range of self‐management behaviours promised by these programmes remain unrealised. This warrants an appraisal of current thinking and the existing evidence to guide the development of programmes better targeted at this age group. Methods: Create a narrative review of systematic reviews produced in the last 3 years that have explored the impact on CYPD of the four key elements of self‐management support programmes: education, instruction and advice including peer support; psychological counselling via a range of therapies; self‐monitoring, including diaries and telemetric devices; and telecare, the technology‐enabled follow‐up and support by healthcare providers. Results: Games and gamification appear to offer a promising means of engaging and educating CYPD. Psychological interventions when delivered by trained practitioners, appear to improve HbA1c and quality of life although effect sizes were small. Technology‐enabled interactive diaries can increase the frequency of self‐monitoring and reduce levels of HbA1c . Telecare provided synchronously via telephone produced significant improvements in HbA1c . Conclusions: The cost‐effective flexibility of increasing the reliance on technology is an attractive proposition; however, there are resource implications for digital connectivity in underserved populations. The need remains to improve the understanding of which elements of each component are most effective in a particular context, and how to optimise the influence and input of families, caregivers and peers.